Extracellular vesicles from fifth-stage larval Angiostrongylus cantonensis upregulate cholesterol biosynthesis and suppress NLRP2-associated inflammatory responses in mouse astrocytes - Chien-Ju Cheng; Lian-Chen Wang; Lichieh Julie Chu; Kuang-Yao Chen; Ching-Yun Huang; Kuo-Lun Lan; Kuo-Yang Huang (mSystems)
ABSTRACT Angiostrongylus cantonensis is a zoonotic parasite that causes severe symptoms in humans, including eosinophilic meningitis and eosinophilic meningoencephalitis. Extracellular vesicles (EVs) derived from helminthes have been implicated in regulating host survival and immune response. However, the roles of A. cantonensis EVs in modulating parasite pathogenesis and host immune response remain poorly understood. Herein, we characterized EVs derived from A. cantonensis fifth-stage larvae (L5) and adult worms. Ultrastructural features showed that EVs from adult worms are smaller in size compared with those from L5. Proteomic analysis identified stage-specific proteins packaged in L5 and adult worm EVs. To investigate the crosstalk between L5 EVs and host cells, RNA sequencing analysis was conducted to identify the differentially expressed genes (DEGs) and enriched biological pathways in mouse astrocytes treated with L5 EVs. GO and KEGG enrichment analysis demonstrated that the pathways related to “cholesterol biosynthesis” are significantly upregulated in L5 EV-treated astrocytes. Based on the transcriptomic data, we observed a downregulated trend of NOD-like receptors (NLRs) protein 2 (NLRP2), a key regulator of brain inflammation, in mouse astrocytes treated with L5 EVs. To validate this result, we utilized ATP to induce the expression of NLRP2 inflammasome-related genes and proteins, as well as the secretion of downstream cytokines. Notably, ATP-induced overexpression of NLRP2 inflammasome-related molecules was significantly reduced in mouse astrocytes upon L5 EV treatment. Collectively, our data suggest that A. cantonensis L5 EVs enhance cholesterol synthesis and potentially modulate immune response by reducing NLRP2 inflammasome-related signaling in non-permissive host cells.IMPORTANCEAngiostrongylus cantonensis is a significant causative agent of eosinophilic meningitis and eosinophilic meningoencephalitis in humans. Helminth-derived extracellular vesicles (EVs) are known to play a crucial role in parasite pathogenesis and host immunomodulation. However, the protein compositions of A. cantonensis EVs and their roles in parasite pathogenesis and host immune response remain unclear. Our results demonstrate for the first time the distinct protein compositions in A. cantonensis L5 and adult worm EVs. The highly abundant proteins in L5 EVs that have immunomodulatory or pathogenic potential in the host deserve further investigation. Additionally, the uptake of L5 EVs by mouse astrocytes significantly upregulates cholesterol synthesis and suppresses ATP-induced NLRP2 inflammasome-related signaling. This study highlights the immunomodulatory roles of L5 EVs in non-permissive hosts, suggesting their potential as therapeutic targets and vaccine candidates against A. cantonensis.